Politik Identitas Pada Pemilihan Kepala Desa - Puansah, Irman; Pulungan, Darman Syah; Sahbana, Ali (Universitas Muhammadiyah Tapanuli Selatan, 2024)
Identity politics is one of the strategies of village head candidates in gaining votes in general election contests in villages. Identity politics has become a tool of struggle for a group of people who want to win in the village head election. Even though identity politics can actually damage democratic values in Indonesia, identity politics in village head elections still often occurs. Of course, if identity politics continues to occur in village head elections, it is feared that dominant groups will suppress minority groups. Identity politics can also divide society because different identities are always emphasized. Based on this, this paper aims to find out what identity politics really is in village head elections, what forms of identity politics occur in villages, and what the impact of identity politics is in villages. The method used in this paper is literature study, collecting information by understanding and studying theories from various literature related to the research. The research results show that identity politics is a tool of struggle and a tool for gaining votes, so it is difficult to avoid. Forms of identity politics include religious identity, ethnicity, clan culture, gender and territorial differences. Identity politics has a negative impact on the sustainability of democracy.Key words: Identity, Village Head Election, Politics.